A Versatile Approach to Engineering Biomolecule‐Presenting Cellular Microenvironments. Issue 2 (7th November 2012) - Lienemann, Philipp S.; Karlsson, Maria; Sala, Ana; Wischhusen, Hanna M.; Weber, Franz E.; Zimmermann, Roland; Weber, Wilfried; Lutolf, Matthias P.; Ehrbar, Martin
<x xml:space="preserve">Abstract</x> By combining a novel protein‐capture hydrogel with state‐of‐the‐art mammalian recombinant protein production, cellular microenvironments are fabricated that locally instruct in‐vitro cell behavior through selective presentation of the expressed proteins. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>